Growth performance, meat quality and lipid metabolism in finishing lambs fed diets containing rumen-unprotected and rumen-protected betaine - Yaqian Jin (Taylor & Francis Group, 2021)
This study investigated the influence of dietary supplementation of rumen-unprotected betaine (RUPB) and rumen-protected betaine (RPB) on growth performance, meat quality and fatty acid profile in intramuscular and subcutaneous fat of growing lambs. A total of 24 Hu male lambs were equally divided into three groups and fed a basal diet or basal diet supplemented with 1.6 g/kg of RUPB or 2.9 g/kg of RPB for 68 days. The water loss, redness of longissimus dorsi (LD) muscle and abdominal fat percentage were reduced in RUPB and RPB groups (p < .05). RPB supplementation decreased the shear force of LD muscle (p < .05). Polyunsaturated fatty acid (PUFA) content in LD muscle was decreased in RPB group, whereas n-3PUFA content was increased in RUPB group (p < .05). RUPB and RPB supplementation reduced the content of saturated fatty acid (SFA), and increased the contents of PUFA, monounsaturated fatty acid (MUFA), and n-6PUFA in subcutaneous fat (p < .05). Furthermore, dietary RUPB and RPB supplementation increased the mRNA expression of acetyl-CoA carboxylase (ACC) and glycerol-3-phosphate acyltransferase 1 (GPAT1) in LD muscle. It increased the mRNA expression of fatty acid synthetase (FANS) and lipoprotein lipase (LPL) but reduced the mRNA expression of GPAT1 in subcutaneous fat (p < .05). In conclusion, either RUPB or RPB supplementation may improve the meat quality and slightly change the fat deposition and fatty acid composition of intramuscular and subcutaneous fat, and RUPB is recommended as a supplement for growing male lambs based on its lower cost.Highlights Dietary supplementation of both rumen-unprotected betaine and (RUP B) and rumen-protected betaine (RPB) improved meat quality and altered the fat deposition of growing male lambs. Both RUPB and RPB supplementation changed fatty acid composition in the longissimus dorsi muscle and subcutaneous adipose tissue. RUPB is recommended as a supplement for growing lambs based on its lower cost.